Perencanaan Pembangunan Pertanian Tanaman Pangan Kabupaten Cilacap - Puspitoarum, Monik Ajeng (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2017)
This paper examines the process of agricultural development planning of food crops in Cilacap Regency and application of innovation in planning. Result of this research indicates that planning process in Cilacap Regency is dominated by technocratic and top-down approach through ‘musrenbang’. The proposed programs and activities generated by technocratic approach are more in numerous comparing to those delivered by musrenbang process. Lack of farmer groups involvement in planning process cause this problem. Development planning of food crops agriculture in Cilacap has not considered innovation optimally in the planning process. The application of technology is carried out as a routine program implementation.